2-Dimensional heat and mass transfer analysis of condensation on channeled coolant plate in air gap membrane distillation (AGMD) freshwater production system - Perves Bappy, Mohammad Jabed; Bahar, Rubina; Ariff, Tasnim Firdaus (2015)
Air Gap Membrane Distillation (AGMD) is making its way into freshwater production systems because of its freedom in choices of coolants and little chance of distillate contamination. The process uses a narrow air gap that separates the hydrophobic membrane and the coolant plate. The use of channelled coolant plates in AGMD is a recent method to enhance the overall production. In this paper, two dimensional heat and mass transfer of vapour condensation on channelled coolant plates of an AGMD system is studied. Investigation on the thermodynamic advantages of using channelled coolant plates over traditional flat plates was carried out. A two dimensional heat and mass transfer model for condensation is developed and compared with available experimental results. A 15cm x 15cm Aluminium coolant plate with rectangular fins has been taken into consideration. Results found from the investigation can be used to design and develop a freshwater supply system with an enhanced rate of water production from household wastewater.